Bacterial Composition, Community Structure, and Diversity in Apis nigrocincta Gut - Christian Apolinaris Lombogia; Max Tulung; Jimmy Posangi; Trina Ekawati Tallei (International Journal of Microbiology)
Understanding the honeybee gut bacteria is an essential aspect as honeybees are the primary pollinators of many crops. In this study, the honeybee-associated gut bacteria were investigated by targeting the V3-V4 region of 16S rRNA genes using the Illumina MiSeq. The adult worker was captured in an urban area in a dense settlement. In total, 83,018 reads were obtained, revealing six phyla from 749 bacterial operational taxonomic units (OTUs). The gut was dominated by Proteobacteria (58% of the total reads, including Enterobacteriaceae 28.2%, Erwinia 6.43%, and Klebsiella 4.90%), Firmicutes (29% of the total reads, including Lactococcus garvieae 13.45%, Lactobacillus spp. 8.19%, and Enterococcus spp. 4.47%), and Actinobacteria (8% of the total reads, including Bifidobacterium spp. 7.96%). Many of these bacteria belong to the group of lactic acid bacteria (LAB), which was claimed to be composed of beneficial bacteria involved in maintaining a healthy host. The honeybee was identified as Apis nigrocincta based on an identity BLAST search of its COI region. This study is the first report on the gut microbial community structure and composition of A. nigrocincta from Indonesia.